Relationships between stroke parameters and critical swimming speed in a sprint interval training set - Barden, J. M.; Kell, R. T. (Journal of Sports Sciences, 2009)
The aim of this study was to determine whether a relationship exists between stroke parameters and critical swimming speed (which is defined as the speed that can theoretically be maintained without exhaustion). Stroke parameters (stroke rate and length) and velocity were recorded for each 25-m length during a controlled sprint interval training set in which participants swam one of the four competitive strokes at a range of intensities below, at, and above critical speed. Eleven participants (8 females, 3 males; age 17.9 ± 0.9 years) completed a progressive (descending) set of 8 100 m repetitions in a 25-m pool according to target times that ranged in intensity from 65% to 100% of the swimmer's best time (the intensity for each repetition increased by 5% throughout the set). The data showed that participants reached critical speed on the fourth repetition and that substantial and unpredictable changes in stroke parameters occurred once critical speed had been reached. Specifically, post-critical speed stroke rate and stroke length were significantly (P < 0.01) greater and less, respectively, than the pre-critical speed values, and these changes occurred in an abrupt and non-linear manner. Overall, the findings suggest that critical speed represents a transition point between two different sets of stroke parameter relationships - one for low-intensity aerobic swimming and one for high-intensity anaerobic swimming.